2021
DOI: 10.1002/adma.202007758
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Materials for Bidirectional Redox‐Based Communication

Abstract: Emerging research indicates that biology routinely uses diffusible redox‐active molecules to mediate communication that can span biological systems (e.g., nervous and immune) and even kingdoms (e.g., a microbiome and its plant/animal host). This redox modality also provides new opportunities to create interactive materials that can communicate with living systems. Here, it is reported that the fabrication of a redox‐active hydrogel film can autonomously synthesize a H2O2 signaling molecule for communication wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…In general, phenazines have more reducing redox-potentials than catechols ( Wang et al., 2021 ) ( Figure 4 A), and we performed redox-probing studies to compare the relative redox-potentials of the PYO-PEG hydrogel reported here with previously reported catechol (CAT)-PEG hydrogels ( Li et al., 2021 ). To generate a CAT-PEG hydrogel that spanned the optical window of the honeycomb electrode of Figure 2 A, we first electro-assembled a PEG-hydrogel using PEG-SH (10 mM), Fc (5 mM) and applying an anodic potential (+0.5 V for 5 min).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, phenazines have more reducing redox-potentials than catechols ( Wang et al., 2021 ) ( Figure 4 A), and we performed redox-probing studies to compare the relative redox-potentials of the PYO-PEG hydrogel reported here with previously reported catechol (CAT)-PEG hydrogels ( Li et al., 2021 ). To generate a CAT-PEG hydrogel that spanned the optical window of the honeycomb electrode of Figure 2 A, we first electro-assembled a PEG-hydrogel using PEG-SH (10 mM), Fc (5 mM) and applying an anodic potential (+0.5 V for 5 min).…”
Section: Resultsmentioning
confidence: 99%
“…A control was prepared by initially poising the hydrogel in its oxidized state (PYO Ox -PEG) by thorough rinsing with air-saturated water. A separate, smaller (diameter: 2 mm) CAT-PEG hydrogel was electro-assembled on a standard gold electrode by immersing the electrode in a solution containing PEG-SH (10 mM) and catechol (30 mM) and imposing a constant oxidative potential (+0.7 V for 1 min) ( Li et al., 2021 ). In our experiment, the CAT-PEG hydrogel is the sink for electrons and was poised in an oxidized state by gently shaking in air for at least 2 h. (Note: we were unable to provide a suitable CAT Red -PEG control because this reduced state was not sufficiently stable to allow a multi-hour sample handling and experimentation.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fc near the surface of the electrode will become oxidized, diffuse away from the electrode surface, and oxidize the free thiol groups of PEG, converting them to sulfenic acid groups. Sulfenic acid groups will react with nearby thiol groups attached to PEG, thus establishing intermolecular bonds allowing a hydrogel to form Li et al, 2021;Raja et al, 2015;Sun & Huang, 2016). The thiolated PEG directly assembles onto gold through the sulfur-gold interactions commonly used for templated assembly on gold.…”
Section: Assembly and Characterization Of The Interfacesmentioning
confidence: 99%